Evaluación de la vegetación urbana en la mitigación de la isla de calor en el casco urbano de la ciudad de Chone - Montesdeoca García, Yudid Alexandra (2024)
The objective of the research was to determine the importance of urban vegetation in mitigating the heat island in the urban area of the city of Chone; using analytical, deductive, statistical methods and observation techniques. To identify the urban vegetation areas, a description of the study area was carried out with information from the GAD, PDOT and PUGS of the canton. Likewise, satellite images were collected and the NDVI was calculated; Urban heat island effects were estimated with respect to downtown temperature using LST calculations and maps representing heat islands were created. Finally, the relationship between the presence of urban vegetation and the effects of the heat island was evaluated using the Pearson correlation with values of -1 and 1 for the NDVI and LST variables. The NDVI results demonstrated significant changes between the years 2016, 2019 and 2023, representing surfaces without vegetation in 2023. Similarly, the land surface temperature showed variations in 2016 with T from 21.39 to 28.86 °C, in 2019 T from 13.66 to 26.18 °C and, in 2023 T from 18.24 to 24.06 °C. Finally, an inversely proportional correlation was found between temperature, LST and NDVI during the mentioned years. It is concluded that, in the period studied, the NDVI showed a low vegetation index in the central area and its surroundings with variations between -0.11 to 0.61.